2020
DOI: 10.3389/fmats.2020.00017
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching in Graphene Oxide

Abstract: The search and investigation of resistive switching materials, the most consolidated form of solid-state memristors, has become one of the fastest growing areas in the field of electronics. This is not only due to the huge commercial interest in developing the so-called Resistive Random-Access Memories (ReRAMs) but also because resistive switching materials are gathering way to new forms of analog computation. Unlike in the field of traditional electronics technologies, where Silicon has monopolized most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…The I-V characteristic of the proposed compact model has high correlation with the experimental data [148,151]. A similar discussion mechanism of bulk GO was also supported by Romero et al [139], whose work mainly focused on different switching mechanisms of GO memristive devices.…”
Section: Metal Filament-based Switching Mechanismsupporting
confidence: 68%
See 3 more Smart Citations
“…The I-V characteristic of the proposed compact model has high correlation with the experimental data [148,151]. A similar discussion mechanism of bulk GO was also supported by Romero et al [139], whose work mainly focused on different switching mechanisms of GO memristive devices.…”
Section: Metal Filament-based Switching Mechanismsupporting
confidence: 68%
“…Several studies reported that the main reason for RS performance in dielectric layers based on graphene and its derivatives, especially GO layers, is the diffusion of oxygen ions or vacancies [19,[134][135][136][137][138][139]. In general, the RS behavior and switching mechanism are influenced by the fabrication methods and hybridization state of graphene-based material dielectric layers, the deposition techniques of electrode layers, and the choice of TE and BE materials.…”
Section: Oxygen Ion-based Switching Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recent (2019-2020) review articles describe all the aspects, starting from fundamentals of resistive switching (RS), mechanisms responsible for switching action, fabrication processes, materials properties, etc., of resistive switching devices for nonvolatile RRAM and computing applications [1][2][3][4][5][6][7][8][9]. Many pure oxide thin film heterostructures, perovskite oxides, metal halide perovskite, manganites, single-crystalline materials, and thin films of chalcogenide semiconductors, organic and hybrid materials including graphene oxide have shown to exhibit resistive switching [1][2][3][4][5][6][7][8][9]. Mixed metal oxide systems such as ferrites (spinels, garnets, orthoferrites, etc.,) exhibiting memory and switching characteristics are of prime significance in the field of digital electronics.…”
Section: Introductionmentioning
confidence: 99%